American (Desolitudes): Henry Thoreau, Ralph Ellison, and Jonathan Lethem - Horton, Jack (Université d'Ottawa / University of Ottawa, 2019)
This dissertation focuses on the works of Henry David Thoreau, Invisible Man by Ralph Ellison, and a wide variety of Jonathan Lethem’s stories. Situating my argument within the nascent field of solitude studies, I argue that solitude has so far been incorrectly defined. It is not loneliness, not alienation or isolation, disenfranchisement, ennui or detachment. I say that solitude is harder to define, and I go further to claim that attempts to define solitude are doomed to fail because of the very nature of solitary practice. Solitude is a praxis through which these authors resist various totalizing narratives that seek to delimit or control bodies. I suggest that solitude as we know it owes its life to Thoreau, but that our understanding of Thoreau’s solitude has been coloured by misinterpretations or misattributions. The hermit’s teachings reject the idea that solitude can be defined by space, time, or friendship. Solitude can be inhibited or promoted by these states, but it is never singularly caused by them. Solitary practice exists on the threshold. Thoreau as a writer had boots on the ground during the beginnings of the industrialization of the American prison system we know today; the insights he was able to glean from seeing firsthand the development of solitary confinement are especially relevant to our encounter with contemporary America. Almost all critics agree that a study of solitude must begin with Thoreau, but almost all of them immediately lose sight of the three main things Thoreau was attempting to do: resist historical hegemony, refuse ‘progress’ a voice, and remind people that however political a discussion, real bodies and real people were victims. Several important contexts inform this study, but the main discussion touches on issues surrounding gentrification, incarceration, trauma and loss, and how writing confronts the unimaginable. In each section of this dissertation I emphasize especially the ontological dimension of solitude—its undeniable body—and the way writing itself can be used to disrupt or confront narrative hegemonies that seek to control or limit. I examine Thoreau’s idea of the threshold, his development of a theory of solitary practice, Ellison’s conscription of solitude as a mode of resistance against dispossessive narratives of historical progress, and Lethem’s beautifully haunting commentaries on individual and national trauma. I situate my discussion of solitude against a number of exigent contemporary issues, especially trauma and prisonhood. The American obsession with incarceration creates and perpetuates traumas both individual and national. I map Thoreauvian solitude against the modernist anti-historicist novel Invisible Man and conclude the discussion by seeing how Jonathan Lethem’s novels, especially those written after 9/11, can further explain and expand our understanding of contemporary solitudes. My argument is not developmental or chronological, other than for convenience. My purpose is not to show that things change over time; however, I do demonstrate the continuities of solitude across the past two centuries. Instead, I am engaged by the idea that solitude is a useful and versatile framework for understanding how authors might resist the prisonization or supermaxing of American culture. These authors, disparate as they might be, are all fascinated by solitude. I ask a series of questions I believe have been overlooked in contemporary Americanist studies of solitude: what happens to solitary bodies; what is going on with incarceration in America; how does solitude help us understand trauma; how does solitude affect writing?
Keywords: solitude